Semantic integrated condition monitoring and maintenance of complex system - Guiyang Jin; Zhanqin Xiang; Fuzhai Lv (2009 IEEE 16th International Conference on Industrial Engineering and Engineering Management, 2009)
Condition monitoring and maintenance system of capital-intensive plant such as energy, chemical and manufacturing is information-intensive. It needs to integrate process parameters (such as speed, flow rate, etc) from process control systems and component condition monitoring parameters (such as vibration, oil particle size, etc) to improve fault detection, fault isolation and fault identification process. It also needs data (such as asset maintenance history information, spare parts, and costs information) from MES or ERP systems to optimize the maintenance activity decision. In this paper, we introduce ontology and rule to code the condition monitoring and maintenance domain knowledge, and then different applications can use tools (rule engine, reasoner) to manipulate the domain knowledge. In this way, it is easy to accomplish the condition monitoring and maintenance activities, reuse and share the domain knowledge.